2002
DOI: 10.1038/sj.sc.3101286
|View full text |Cite
|
Sign up to set email alerts
|

Intensive exercise may preserve bone mass of the upper limbs in spinal cord injured males but does not retard demineralisation of the lower body

Abstract: Study design: Cross-sectional study comparing a group of active spinal cord injured (SCI) males carefully matched for age, height, and weight with active able-bodied male controls. Objectives: To compare bone mass of the total body, upper and lower limbs, hip, and spine regions in active SCI and able-bodied individuals. Setting: Outpatient study undertaken in two centres in New Zealand. Methods: Dual energy X-ray absorptiometry (DEXA) scanning was used to determine bone mass. Questionnaires were used to ascert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(37 citation statements)
references
References 35 publications
2
34
0
1
Order By: Relevance
“…5,16,17 An alternative is to measure length. Jones et al 21 reported the Pearson's correlation coefficient for height (measured by wall-mounted stadiometer) versus length (by the electronic ruler function of DXA) to be 0.996 (P ¼ 0.0001). Buchholz et al 22 found the coefficient of variation between height (by wall-mounted stadiometer) versus length (by length board) to be 0.870.02% (mean7SD, NS).…”
Section: Body Mass Index (Bmi) As a Marker Of Obesity In Chronic Scimentioning
confidence: 99%
“…5,16,17 An alternative is to measure length. Jones et al 21 reported the Pearson's correlation coefficient for height (measured by wall-mounted stadiometer) versus length (by the electronic ruler function of DXA) to be 0.996 (P ¼ 0.0001). Buchholz et al 22 found the coefficient of variation between height (by wall-mounted stadiometer) versus length (by length board) to be 0.870.02% (mean7SD, NS).…”
Section: Body Mass Index (Bmi) As a Marker Of Obesity In Chronic Scimentioning
confidence: 99%
“…These changes are associated with increased risk for pathological fractures, nephrolithiasis, nephrocalcinosis, frank hypercalcemia, and heterotopic ossification at the knees (5-7). The effects of exercise and muscle contractions on bone mineral density in patients with SCI are contradictory and as yet unproven (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…21 Paradoxically, at the lumbar spine, which is mainly constituted of trabecular bone, no reduction in BMD occurs whatever the lesion level or postinjury duration. 1,3,11,[16][17][18][22][23][24][25][26][27][28][29][30][31] This has been demonstrated to be due to continuous body weight-bearing during wheelchair use. 1,11,23,24 However, it should be kept in mind that in certain cases, BMD at the lumbar spine can be 'falsely increased' by neuropathic spondylopathy.…”
Section: Introductionmentioning
confidence: 99%